Language and Culture, English as a Second Language 5110.14 - Plasencia, Piedad; Dade County Public Schools, Miami, FL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
This course concerns several grammatical points as well as the cultural topic of holidays. The language aspect emphasizes the use of dependent clauses, some irregular verbs, comparison of adjectives and adverbs, and intonational variations. Certain library skills, such as using the card catalog and appropriate reference books, are also practiced. The cultural issues in the course require that students be able to identify and describe, both orally and in writing, important holidays. Teaching strategies to accomplish stated objectives are suggested, and resources for both teachers and students are listed. (VM)
ERIC Note: An authorized Course of Study for the Quinmester Program.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Course Descriptions; Cultural Activities; Cultural Education; Educational Objectives; Educational Resources; Educational Strategies; English (Second Language); Grammar; Instructional Materials; Language Instruction; Learning Activities; Second Language Learning; Teaching Methods; Quinmester Program